Muscle stiffness of the vastus lateralis in sprinters and long-distance runners - Miyamoto, N.; Hirata, K.; Inoue, K.; Hashimoto, T. (Medicine & Science in Sports & Exercise, 2019)
Purpose The stiffness of muscle-tendon units and of tendons in the lower legs plays important roles in sprinting and long-distance running. However, the association of muscle stiffness with sprinting and running remains unknown. This study aimed to identify the characteristics of muscle stiffness in sprinters and long-distance runners, and to determine how muscle stiffness is related to the performance of these athletes.